A Prospective Observational Study about Prevalence, Comorbidities, Treatment Modalities, and Drug-drug interactions among Anaemic Inpatients at a Government Medical College Hospital in Tamil Nadu - Arumugavignesh, Murugakadavul; Alexander, Jessica Paul; Abdulla, Mohamed Sali; Sreekumaran, Akshara; Palani, Jeevitha Lakshmi (Indian Journal of Pharmacy Practice)
Objectives: Anaemia is a well acknowledged nutritional deficiency disorder in the world. This study is pivoted on to examine the prevalence of anaemia among hospitalized inpatients and classifying them according to WHO’s severity index with little insight on drugs used to treat anaemia and drugs interacting with haematinics. Materials and Methods: A study of prospective observational nature was carried out between July 2022 and September 2022 in a government district headquarters medical college hospital of Tamil Nadu. The demographic and other data collected for this study includes age, sex, clinical laboratory profiles, diagnostic findings, drugs administered etc. Among lab profiles, hemoglobin, red blood cells, and packed cell volume were segregated. The collected data were segregated with the help of Microsoft Excel 2007 spreadsheets. Drug interactions in prescriptions were found using Micromedex drug interactions checker application. Results: Totally hundred inpatients diagnosed with anaemia were there in our study. Out of 70 female inpatients, 36 (51.42%) were women in child-bearing age (15 – 49 years). Among 100 inpatients, 36 were mildly anaemic, followed by 30 in moderate index, 22 in severe index, and 12 in life-threatening anaemia index. Chronic kidney disease is the most common co-morbidity. Fluroquinolone antibiotics (ofloxacin and ciprofloxacin) were the most common drugs interacting with prescribed iron products in our study. Conclusion: Growing global burden of anaemia is threatening. Drug-drug interactions are often double-edged swords. Educating health-care practitioners about drug-drug interactions and making them aware about clinical management strategies in order to eschew from untoward effects of interactions is an absolute requisite.
Keywords: Anaemia; Haemoglobin; Co-morbidities; Haematinics; Drug-drug interactions; Fluroquinolones